Protective effects of Pluchea lanceolata on dementia induced by omeprazole in experimental rats - Asirvatham, Raju; Prasad Nediyara, Priya; Pa, Daiay; John G, Boby (Journal of Cellular Neuroscience and Oxidative Stress, 2022)
Omeprazole is the most commonly used proton pump inhibitor (PPI), a prospective cohort study reported that chronic use of PPI’s cause dementia. The present study aimed to evaluate the protective effect of hydro alcoholic extract of Pluchea lanceolata (HAEPL) on dementia induced by omeprazole in experimental rats. Total 42 trained rats were divided into 7 groups, each group with six rats. First group received normal food and water for 21 days. Three groups of animals treated with 20mg/kg of omeprazole for 7, 14 and 21 days respectively. Another three groups of animals received 400mg/kg of HAEPL + 20mg/kg of omeprazole for 7, 14 and 21 days respectively. Behavioural studies were conducted on 0th, 7th, 14th and 21st days of treatment by using actophotometer, elevated plus maze (EPM) and cook’s pole climbing apparatus. The next day of behaviour study respective group animals were sacrificed, brain was isolated for estimation of antioxidant, neurotransmitters and histopathological studies. Locomotor activity, number of entry into open arms and time taken to climb the poles were significantly reduced in 20 mg/kg of omeprazole treated rats whereas activity, learning, memory were restored in 400mg/kg of HAEPL treated rats with respect to duration of exposure. Alteration of antioxidant enzyme, neurotransmitter level and histopathological events were found with disease control rats which also corrected by the administration of 400mg/kg of HAEPL. Co-administration of P, lanceolata extract diminishes the progress of dementia caused by omeprazole and may be a potential corner stone in the treatment strategies for researchers and clinicians.
Keywords: Omeprazole; dementia; Pluchea lanceolata; antioxidants; neurotransmitters; Toxicology; Toksikoloji; 3. Good health